Growth of Indian Rural Market : An Invitation to FMCG Sector - Kesari, Rajesh (Journal of Commerce and Trade, 2011)
Fast moving consumer goods (FMCG) have attracted Indian villagers, when the urban demands for the goods are getting saturated, the manufacturing companies look at this development as an opportunity, Large FMCG companies including multinational companies (MNC) are planning their own strategies to enter this large and developing rural market. The marketing strategies have to be tailer made to suit rural conditions the FMCG producers now realize that there is a lot of opportunity for them to enter into the rural market. The sector is excited about the rural population whose incomes are rising and the life styles are changing there are as many middle income house holds in the rural areas as there are in the urban. The FMCG sector has been successful in selling products to the lower and middle income groups and the same is true in India. Over 70% sales is made to middle class households to day and over 50% of the middle class in rural India. Many companies in the FMCG sector in India have taken up a developmental approach to nourish this new market. This paper covers to rural, the challenges, the difference between the rural and the urban market and the suitable marketing strategy with suitable example of companies and their experience in going rural.